“Children of the heart”. Production of adoptive mothers and fathers in Chihuahua Mexico - Chacón Venzor, Ivonne (Revista de Antropología Social, 2022)
In Mexico, biological reproduction continues to be highly valued, therefore, making the decision to adopt and become parents through adoption requires a great effort. In this work, the reproductive experiences of a group of people from two cities in northern Mexico who opted for adoption are analyzed. Their practices and discourses are placed in the context of the policies and rhetoric on reproduction present at both the national and international levels This shows that the process of building a family through adoption is part of a reproductive governance mechanism –a concept coined by Morgan and Roberts– which operates from the global level promoting and giving legitimacy to national reproductive policies that, in turn, affect individual behaviors and decisions in order to produce male and female reproductive subjects in accordance with a certain reproductive morality.